Desenvolvimento de aplicativo Excel/VBA para estimativas de propriedades físicas e termodinâmicas utilizando grupos funcionais - Oliveira, Fernanda da Silva (2017)
The objective of this work was to develop a computational tool in Visual Basic Applications (VBA) programming language which using contribution of functional groups be able to predict the physical properties (critical temperature, critical volume, normal boiling temperature, melt temperature and Surface tension); thermodynamics properties of the ideal gas (enthalpy formation, Gibbs free energy of formation and coefficients of the polynomial equation of heat capacity, vapor pressure and enthalpy of vaporization; molecular structure (area and volume of van der Waals) and activity coefficient. Moreover, the program, named EPCGF, Estimation of Properties by Contribution of Functional Groups, can be used in troubleshooting vapor – liquid equilibrium by the UNIFAC method: estimation of the coefficient of activity at infinite dilution (used for azeotropy verification); deviations from Raoult's law (positive and negative); T bubble, P bubble, T dew and P dew, and three types of flash (isothermal flash, specifying yi and T, and specifying yi and P). The work was divided into eight modules, for each module was created: databases containing the parameters of the contribution models of functional groups; dialog boxes so that there is user interaction with the program; modular coding of VBA subprograms for estimation properties physical, thermodynamic, molecular structures and problems to liquid-vapor equilibrium. After the application construction, validations of the various VBA encodings were made, comparing the results provided by the proposed application with reported in the world literature. The final result of the project is a computational application for educational and / or industrial purposes, being able to perform several predictions of physical and thermodynamic properties quickly and reliably. Therefore, the computational application provides the user, the features of a program with consistent appearance and command structure, which makes it easier to use and learn.